Analysis of the Aggregate Heuristic Planning for Planning and Controlling the Amount of Production to Minimize Costs - Magdalena, Riana (Indonesian Operations Research Association (IORA), 2020)
PT.XYZ is one of the companies engaged in the automotive manufacturing industy, where it produces spare parts for cars, motorcycles and trucks. Along with marketing and producing the products, PT.XYZ continues to implement customer satisfaction and the quality of spare parts produced. The company must anticipate the possibility of production capacity limitations; this must be done as well as possible at the minimum cost. For that, the aggregate heuristic planning is proposed for planning the establishment of a level for production capacity to meet the level of demand obtained from orders with the aim of minimizing total production costs. Aggregate Planning is a process of determining the level of overall production capacity to meet the level of demand obtained from forecasting and order with the aim of minimizing the total cost of production. In this study, three heuristic methods were tried, namely labor control method, subcontracting mixed method, and overtime mixed methods. Based on the results of the study it is known that the subcontracting mixed method is the best method with total aggregate cost of IDR 3,080,689,770, then the labor control method with a total of aggregate cost of IDR 3,080,798,198 and the overtime mixed method, with a total aggregate cost of IDR 3,081,815,315.